NILAI TUKAR NELAYAN USAHA PANCING ULUR DI DESA MANTEHAGE BUHIAS KECAMATAN WORI KABUPATEN MINAHASA UTARA - Bigbraian Talu; Jeannette F. Pangemanan; Florence V. Longdong; Djuwita R.R. Aling; Victoria E.N. Manoppo; Christian R. Dien (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2023)
Abstract Mantehage Buhias Village is located on Mantehage Island, Wori District, North Minahasa Regency which has an area of 631 Ha. The boundaries of the village area are: Mantehage Tangkasi Village to the North, Mantehage Tinongko Village to the South, Sea to the East, Mantehage Bango Village to the West. How is the situation in Mantehage Buhias Village regarding the exchange rate of fishermen in the hand line business and the income and expenses of fishing communities? This is the writer's attention to conduct research. Data collection was carried out by census, where the population in this study were traditional fishing line operators in Mantehage Buhias Village, Wori District, North Minahasa Regency. The census taking method is a data determination technique when all members of the population are used as respondents. In analyzing the data, it was carried out in a qualitative descriptive manner to describe statements using sentences or the author's own feelings, while quantitative descriptive was to provide results through calculations, such as addition using tools/additional tools. After all the data has been collected, the writer will use the NTN and INTN formulas in the solution. The total income of traditional fishing businesses using hand line fishing gear in Buhias Village, Wori District, North Minahasa Regency can cover the basic needs of fishing families. With a NTN of 1.09 while fishermen's income can cover the business costs of traditional hand line fishing with an NTN of 1.38. Observations and calculations in November and December 2022 did not experience a decrease or increase in total NTN revenue, so it remained at the income standard with an INTN value of 100. Keywords: NTN; INTN; Mantehage Buhias Â  Abstrak Desa Mantehage Buhias terletak di Pulau Mantehage, Kecamatan Wori Kabupaten Minahasa Utara yang memiliki luas wilayah sebesar 631 Ha. Batas-batas wilayah desa yakni: Sebelah Utara dengan Desa Mantehage Tangkasi, Sebelah Selatan dengan Desa Mantehage Tinongko, Sebelah Timur dengan Laut, Sebelah Barat dengan Desa Mantehage Bango. Bagaimana keaadan di Desa Mantehage Buhias mengenai nilai tukar nelayan usaha pancing ulur serta pendapatan dan pengeluaran masyarakat nelayan? Hal tersebut menjadi perhatian penulis untuk melakukan penelitian. Pengambilan data dilakukan secara sensus, dimana populasi dalam penelitian ini adalah pelaku usaha nelayan tradisional pancing ulur di Desa Mantehage Buhias, Kecamatan Wori, Kabupaten Minahasa Utara. Metode pengambilan sensus merupakan teknik penentuan data bila semua anggota populasi digunakan sebagai responden. Dalam menganalisis data dilakukan secara deskriptif kualitatif untuk mengambarkan keterangan-keterangan menggunakan kalimat atau perasaan penulis itu sendiri, sedangkan deskriptif kuantitatif untuk memberikan hasil melalui perhitungan, seperti penjumlahan dengan menggunakan alat bantu/tambahan. Setelah data terkumpul semua maka penulis akan menggunakan rumus NTN dan juga INTN dalam penyelesaiannya. Pendapatan total usaha nelayan tradisional dengan menggunakan alat tangkap pancing ulur di Desa Buhias Kecamatan Wori Kabupaten Minahasa Utara dapat menutupi kebutuhan dasar keluarga nelayan. Dengan NTN sebesar 1,09 sedangkan pendapatan nelayan dapat menutupi biaya usaha nelayan tradisional pancing ulur dengan NTN sebesar 1,38. Pengamatan dan perhitungan pada bulan November dan Desember 2022 tidak mengalami penurunan ataupun kenaikan pada total pendapatan NTN, sehingga tetap berada pada standar pendapatan dengan nilai INTN sebesar 100. Kata Kunci: NTN; INTN; Mantehage Buhias